Hubungan antara Self-Efficacy dengan Kecemasan Menghadapi Ujian Skripsi pada Mahasiswa Psikologi Universitas Muhammadiyah Surakarta - Wardhani, Dewi Kusuma; , Dra. Partini, M.Si (2015)
One of the tasks the student is able to complete the thesis and thesis exams with good, but not a few students that the exam essay have anxiety. One of the factors that influence the anxiety an exam essay is self-efficacy. The purpose of this study were 1) To know the relationship between self-efficacy with anxiety for exams thesis, 2) Determine the level of self-efficacy, 3) Knowing the anxiety level of the exam thesis, 4) Knowing the role of self-efficacy against anxiety for exams thesis on student UMS psychology . This study used 221 UMS psychology student population and as many as 43 were used as a sample. The research method uses a quantitative approach with a scale measuring self-efficacy and anxiety scale essay exams. Data analysis technique uses Pearson Product Moment. Based on the analysis of data obtained korelasir_xy coefficient = -0.387 with sig = 0.005, p <0.01. So the hypothesis is accepted, it can be said there is a significant negative relationship between self-efficacy with exam anxiety thesis. Level of self-efficacy in the high category with an average empirical (RE) 85.30 and the average hypothetical (RH) 67.5. Anxiety level exams thesis belong to the medium category with an average empirical 74.65 (RE) and the average hypothetical (70). The effective contribution of self-efficacy with anxiety faced thesis examination by 14.97% and 85.03% were influenced by other variables. Keywords: self-efficacy, anxiety essay exams